(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
This article talks about the importance of spiritual and moral factors in the formation of relations between generations. The factors of formation of spiritual and moral values throughout the entire period of child development are studied by a number of modern sciences. In this regard, the task of spiritual and moral education in the aspect of intergenerational relationships is of extreme importance: it must be understood today as one of the priorities in the development of our state